Provenance and paleoclimate of Middle Permian Tavantolgoi formation sandstones in Baruunnaran coal deposit, southern Mongolia - Batbold, Demberelsuren; Jargal, Luvsanchultem; Dashpuntsag, Nansalmaa; Maibayar, Otgonsuren (Geological Issues, 2023)
Baruunnaran coal deposit is located in southern Mongolia; belongs to Tavantolgoi coal zone of South Gobi Basin (Bat-Erdene, 1992). Coal seams are hosted by Middle Permian Tavantolgoi Formation which is subdivided into lower and upper member, based on lithological characteristics. Ten core samples, consisting of sandstones were collected from exploration drill holes. Sandstones from Middle Permian Tavantolgoi Formation in Baruunnaran coal deposit are investigated for unravel their provenance and paleoclimate conditions andtectonic settings. Detrital modes of sandstones in lower member are characterized as slightly high amount of mineral grains (quartz and feldspar) and slightly low amount of lithic fragments (litharenite, feldspathic litharenite and lithic arkose) comparing to sandstones from upper member (litharenite and lithic arkose). Provenance study of sandstones are shown signature of recycled orogens and mixed orogenic sands. Whereas, paleoclimate condition of sandstones from lower and upper members are interpreted as they were deposited in semi humid and arid environments, respectively.